2020
DOI: 10.1097/ta.0000000000002620
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative endovascular balloon occlusion of the aorta in a pediatric swine model: Is 60 minutes too long?

Abstract: BACKGROUND Resuscitative endovascular balloon occlusion of the aorta (REBOA) is recommended in adults with a noncompressible torso hemorrhage with occlusion times of less than 60 minutes. The tolerable duration in children is unknown. We used a pediatric swine controlled hemorrhage model to evaluate the physiologic effects of 30 minutes and 60 minutes of REBOA. METHODS Pediatric swine weighing 20 kg to 30 kg underwent a splenectomy and a controlled 60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…50 Although there is a relatively robust and growing body of literature in the adult trauma population, the published experience with REBOA in the pediatric population is primarily limited to animal models, radiologic mapping/measuring for theoretical deployment, and case reports. [50][51][52][53][54] Several larger case series using national databases or registries have been published, but the analysis of pediatric REBOA use and outcomes have been almost exclusively in the adolescent/young adult age range of 16 to 18 years. 50,54,55 Given the lack of data and experience with REBOA in the true pediatric age range the group consensus was to not include it as a recommended option or pathway in this algorithm.…”
Section: Areas Of Controversy and Existing Knowledge/research Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Although there is a relatively robust and growing body of literature in the adult trauma population, the published experience with REBOA in the pediatric population is primarily limited to animal models, radiologic mapping/measuring for theoretical deployment, and case reports. [50][51][52][53][54] Several larger case series using national databases or registries have been published, but the analysis of pediatric REBOA use and outcomes have been almost exclusively in the adolescent/young adult age range of 16 to 18 years. 50,54,55 Given the lack of data and experience with REBOA in the true pediatric age range the group consensus was to not include it as a recommended option or pathway in this algorithm.…”
Section: Areas Of Controversy and Existing Knowledge/research Gapsmentioning
confidence: 99%
“…One approach that has been proposed as a safer and less invasive alternative to ERT is REBOA 50 . Although there is a relatively robust and growing body of literature in the adult trauma population, the published experience with REBOA in the pediatric population is primarily limited to animal models, radiologic mapping/measuring for theoretical deployment, and case reports 50–54 . Several larger case series using national databases or registries have been published, but the analysis of pediatric REBOA use and outcomes have been almost exclusively in the adolescent/young adult age range of 16 to 18 years 50,54,55 .…”
Section: Areas Of Controversy and Existing Knowledge/research Gapsmentioning
confidence: 99%
“…Another study [ 2 ] showed that a single continuous occlusion duration longer than 90 min caused significant complications, while the overall damage was minor when the occlusion time was less than 90 min. In some animal studies of hemorrhagic shock, occlusion times of 60 or 90 min were associated with substantial ischemia and reperfusion injury (IRI), which increases late mortality [ 8 12 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that REBOA catheters are being used in pediatric patients, particularly adolescents. In pre-clinical studies, REBOA has been shown to decrease blood loss in a pediatric swine model [7], and pediatric swine have been found to tolerate 30 minutes, but not 60 minutes, of complete aortic occlusion [8]. However, there is no consensus on indications for REBOA use in pediatric patients at this time and more data is needed on the outcomes of pediatric patients undergoing REBOA placement to guide future use.…”
Section: Introductionmentioning
confidence: 99%